PENGARUH SISTEM PENGENDALIAN INTERNAL, PENERAPAN GOOD CORPORATE GOVERNANCE (GCG), DAN PEMANFAATAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN - elina elina (SCIENTIA JOURNAL, 2026)
This study examines factors influencing the quality of financial statements in companies. The objective of this research is to analyze the effect of internal control systems, the implementation of Good Corporate Governance, and the use of accounting information systems on financial statement quality. A quantitative approach was employed by collecting primary data through questionnairesl distributed to individuals involved in the preparation and management of financial reports. The research population consisted of 22,082 companies located in Batam City that possess a Business Identification Number, and the sample was determined using the Slovin formula, resulting in 100 companies, each represented by one accounting staff member. Data were analyzed using SPSS version 26. The results indicate that, partially, the internal control system does not have a significant effect on financial statement quality, while Good Corporate Governance and the use of accounting information systems have a significant positive effect. Simultaneously, internal control systems, Good Corporate Governance, and accounting information systems significantly influence financial statement quality. These findings suggest that improving financial statement quality requires strengthening corporate governance practices and optimizing thel use of accounting information systems